2004
DOI: 10.1021/ma035468b
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Chain Transfer Agents for Reversible Addition Fragmentation Chain Transfer (RAFT) Polymerization to Synthesize Functional Polymeric Architectures

Abstract: We report the syntheses and uses of versatile chain transfer agents (CTAs) that produce well-controlled macromolecular architectures with specific chain-end functionalities, via reversible addition fragmentation chain transfer (RAFT) polymerization). Examples of architectures are given, including amphiphilic copolymers and block copolymers incorporating a biodegradable block. These CTAs are also used for the grafting of poly(styrene), poly(methyl methacrylate) and poly(methyl acrylate) from cotton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
203
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(206 citation statements)
references
References 28 publications
3
203
0
Order By: Relevance
“…[77,110] We first exploited this methodology to prepare poly(ethylene oxide)-block-PS from commercially available hydroxy end-functional poly(ethylene oxide) (last example in Table 12). [77,110] Other block copolymers that have been prepared using similar strategies include poly(ethylene-co-butylene)-blockpoly(S-co-maleic anhydride), [70] poly(ethylene oxide)-blockpoly(MMA), [204] poly(ethylene oxide)-block-poly(N-vinylformamide), [205] poly(ethylene oxide)-blockpoly(NIPAM), [206] poly(ethylene oxide)-block-poly(1,1,2,2-tetrahydroperfluorodecyl acrylate), [207] poly(lactic acid)-block-poly(MMA), [204] and poly(lactic acid)-blockpoly(NIPAM). [208,209] …”
Section: Diblock Copolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…[77,110] We first exploited this methodology to prepare poly(ethylene oxide)-block-PS from commercially available hydroxy end-functional poly(ethylene oxide) (last example in Table 12). [77,110] Other block copolymers that have been prepared using similar strategies include poly(ethylene-co-butylene)-blockpoly(S-co-maleic anhydride), [70] poly(ethylene oxide)-blockpoly(MMA), [204] poly(ethylene oxide)-block-poly(N-vinylformamide), [205] poly(ethylene oxide)-blockpoly(NIPAM), [206] poly(ethylene oxide)-block-poly(1,1,2,2-tetrahydroperfluorodecyl acrylate), [207] poly(lactic acid)-block-poly(MMA), [204] and poly(lactic acid)-blockpoly(NIPAM). [208,209] …”
Section: Diblock Copolymersmentioning
confidence: 99%
“…The synthesis of star polymers from multi-RAFT agents can be seen as an extension of the triblock syntheses described above where the number of thiocarbonylthio groups exceeds two. The multi-RAFT agent may be a small organic compound, [6,9,77,110,198,[212][213][214] an organometallic complex, [215] a dendrimer, [216][217][218] a hyperbranched species, [219] a macromolecular species, [204,220] a particle, or indeed, any moiety possessing multiple thiocarbonylthio groups (though here the distinction between star and graft copolymers becomes blurred). Our first RAFT patent [14] recognized two limiting forms of star growth depending on the orientation of the thiocarbonylthio group with respect to the core.…”
Section: Star Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAFT agents utilized in this study are those reported recently by Perrier and co-workers for the polymerization of styrene, (meth)acrylates and acrylates. [80] Polymerization of THPA was performed at 70 8C using azobisisobutyronitrile (AIBN) as a radical initiator (Scheme 2). IR and 1 H NMR spectroscopic analyses indicated that the degree of ester deprotection was low (ca.…”
mentioning
confidence: 99%
“…The synthetic methods of these esters type compounds are convenient and easy to introduce the functional groups. 13,14,27,28 The various substituents at the a-carbon of the carbonyl group contribute toward the stabilization of the radical intermediate (Scheme 1, I, II), and also lead to generate radicals of various stabilities during the addition-fragmentation step shown in Scheme 1. 29 The reported efficiency of ester leaving groups (Scheme 2) for the polymerizations of styrene (St), acrylates, and methacrylates is shown in the following order: E1 < E2 < E3 < E4.…”
Section: Introductionmentioning
confidence: 99%